A review on human intent understanding and compliance control strategies for lower limb exoskeletons. (July 2022) - Yang, Jiantao; He, Yong; Shi, Ping; Yu, Hongliu
The exoskeleton has emerged as a promising technology to enhance humans' strength and boost users' efficiency. In order to provide congruent human–machine interaction for assisting the users, exoskeletons should have knowledge of human's planned action and accordingly command the robot by the designed controller. It means the ubiquitous aspect of exoskeletons lies on motion intent understanding and active compliance control. In the last decade, extensive research has been conducted on the two topics. However, no major breakthrough has been made. Thus, a systematic review and analysis on this very subject is of great significance in developing exoskeletons. Within this context, this review first surveys the history of lower limb exoskeletons to summarize the various technologies for realizing transparent human exoskeleton coordination. Then, an overview about motion intent understanding and compliance control strategies are presented in detail. Furthermore, the future trend and research directions are also outlined.